2018
DOI: 10.1007/s12010-018-2734-2
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-499a-5p Promotes Differentiation of Human Bone Marrow-Derived Mesenchymal Stem Cells to Cardiomyocytes

Abstract: Since the adult mammalian heart has limited regenerative capacity, cardiac trauma, disease, and aging cause permanent loss of contractile tissue. This has fueled the development of stem cell-based strategies to provide the damaged heart with new cardiomyocytes. Bone marrow-derived mesenchymal stem cells (BM-MSCs) are capable of self-renewal and differentiation into cardiomyocytes, albeit inefficiently. MicroRNAs (miRNAs, miRs) are non-coding RNAs that have the potential to control stem cell fate decisions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…MSCs have been manipulated in vitro to alter the expression of various myo-miRs (myocardium-related miRs) including miR-1, miR-133, miR-208, and miR-499 to enhance their cardiac differentiation [98][99][100]. A recent study has explored an interesting aspect of myo-miRs regarding their exosome-encapsulated release from the infarcted heart (except for miR-133 which is partially released in the exosomes) that gets transferred to the BM mononuclear cells [101].…”
Section: Manipulation Of Mscs To Enhance Exosomal Mir Payloadmentioning
confidence: 99%
“…MSCs have been manipulated in vitro to alter the expression of various myo-miRs (myocardium-related miRs) including miR-1, miR-133, miR-208, and miR-499 to enhance their cardiac differentiation [98][99][100]. A recent study has explored an interesting aspect of myo-miRs regarding their exosome-encapsulated release from the infarcted heart (except for miR-133 which is partially released in the exosomes) that gets transferred to the BM mononuclear cells [101].…”
Section: Manipulation Of Mscs To Enhance Exosomal Mir Payloadmentioning
confidence: 99%
“…This might be attributed to the fact that the miRNA concentrations used in this study are not sufficient to significantly increase the expression level of cardiac-specific genes, although uptake efficiency for miRNA was about 80%. In this regard, some studies have used viral vectors to ensure constitutive overexpression of miRNA [25,64]. Given that miRNAs have a very short half live, transient transfection approaches, as used in our study, might be less effective.…”
Section: Discussionmentioning
confidence: 98%
“…Myo-miRNA based programming has been successfully applied for the conversion of cardiac fibroblasts, into cardiomyocytes [36]. For MSCs, cardiac induction by miRNA is less efficient as shown by different groups [25,63,64]. For example, it was demonstrated that transfection with miRNA-1-2 promote the expression of GATA4, NKX2.5 and cardiac Troponin in BM MSCs [15].…”
Section: Discussionmentioning
confidence: 99%
“…Asymptomatic carotid stenosis [63], cardiac amyloidosis [150], heart failure [151], atherosclerosis [152,153], aortic stenosis [154], acute myocardial infarction [155], acute ischemic stroke [156], focal cerebral ischemia [157], pulmonary artery hypertension [158], obesity [159] hsa-miR-342-3p 14q32.2 Cardiac amyloidosis [150], obesity [160], T1DM [52,149,161], T2DM [149,162,163], GDM [149], endothelial dysfunction [164] hsa-miR-499a-5p 20q11. 22 Myocardial infarction [17,165], hypoxia [166], cardiac regeneration [167], vascular endothelial dysfunction [15] hsa-miR-574-3p 4p14 Myocardial infarction [168], coronary artery disease [100], cardiac amyloidosis [150], stroke [169], T2DM [104,170]…”
Section: Introductionmentioning
confidence: 99%